Awareness of and support for speech, language and communication needs in children's hearings - Ann Clark; Dermot Fitzsimons (Scottish Journal of Residential Child Care)
Looked-after children commonly experience speech, language and communication needs (SLCN) (McCool & Stevens, 2011; Department for Education, 2017). Unidentified and unmet SLCN have negative effects on children's educational attainment as well as social, emotional and mental health (Law, Rush, Parsons & Schoon, 2009). In Scotland, the institutional body with primary responsibility to address the needs of looked-after children is Children's Hearings Scotland (CHS). The focal means of decision-making is the Hearing. Previous FOI requests showed very few referrals from the Hearings to SLT services (Clark & Fitzsimons, 2016). Panel Members' and Children's Reporters' views on children's SLCN and on support for these needs in Hearings were gathered using an online questionnaire. 35 responses were received. Findings emphasised the importance of a child's individual needs. Many respondents had concerns over a child's communication during the Hearings process. SLTs rarely attend Hearings. Barriers to effective communication were seen to be intrinsic to the child, but also within the environment. The paper concludes that an increased role for SLTs within the Hearings System would be beneficial, both working directly with children to support their SLCN, and training and supporting decision makers in developing confidence to refer children to SLT services.